KONSEP COORPORATE SOCIAL RESPONSIBILITY DALAM MEWUJUDKAN KEADILAN DALAM PERSPEKTIF ISLAM - Ardiansyah Ardiansyah (Al-'Adl, 2019)
The concept of Corporate Social Responsibility in Indonesia has not run effectively, CSR is a form of the company's commitment to participate in sustainable economic development to improve the quality of life and benefits that are beneficial, both for the company itself, the local community, and society in general. the implementation of CSR aims to enable the company to carry out its business activities properly and minimize the risks that arise from the surrounding community and from the environment in which they conduct business activities. This paper is a literary study that will raise the concept of CSR in relation to the concept of justice in Islamic perspective, from here the author tries to review this CSR concept with the concept of justice in Islamic perceptions where Islam is fair in all forms of business and business not just achieving profit for employers but also the responsibility to the community and the environment for balance.